Implementation of an intelligent web photo album - Tan, Lee Teng. (2010)
Web photo albums are a growing trend along with the rapid advancement of digital photography technology. With cumulative growing collection of web photos, managing them is a challenging task. Current web photo album solutions proved that there are still many rooms for improvement for this technology. Therefore through the application of novel machine learning and data mining techniques, the author hopes to create an intelligent web photo album using face techniques such as face detection and recognition. The successful implementation of the web photo album in this project will not only bring about more convenience to users who perform online face search frequently but also a breakthrough to the face search engine technology.